Christian spirituality : an introduction - McGrath, Alister E., 1953- (Malden, MA, Blackwell Publishing, 1999)
"This text meets the need for a clear, informative, helpful and well-written introduction to Christian spirituality. It introduces this area of Christian theology as a serious and exciting area of study to those encountering it for the first time. It builds on the huge success of earlier texts in the area of Christian thought and practice by the same author, and is based on seven years' experience of teaching its themes."--Jacket.
"Written in a clear and accessible manner, and tested in the classroom, this text adopts the highly praised educational approach embodied in other best-selling texts by the same author; avoids a purely historical approach to the subject which students might find unrewarding; encourages active engagement with primary sources through worked case studies; includes a major analysis of the relationship between theology and spirituality, focusing on five major themes; offers complete coverage of the Christian spiritual tradition, including Catholicism, Orthodoxy, Protestantism and Evangelicalism; includes a guide to resources in spirituality available on the Internet; can be used for private study or taught courses."--Jacket.
Introduction -- Types of Christian spirituality -- Theological foundations for spirituality : basic issues -- Theological foundations for spirituality: case studies -- Biblical images and Christian spirituality -- Faces, places, and spaces: visualization and spatialization in Christian spirituality -- Christian spirituality: engaging the tradition.
Includes bibliographical references (pages 198-201) and index.
Keywords: Spirituality